Alice in wonderland - Carroll, Lewis, 1832-1898. (New York : Penquin Classics, 2003)
A little girl falls down a rabbit hole and discovers a world of nonsensical and amusing characters.
"Ages 8-12"--cover p. [4].
Keywords: Fantasy